Social Sigma as a Predictor of Perceived Stress Among Parents of Children with Special Needs - Kausar, Noreena; Mazhar, Maria; Rizwan, Safa (Journal of Peace, Development and Communication, 2021)
Current study was designed with the aim to explore the relationship between perceived social stigma(PSS) and perceived stress(PS) among parents of children with special needs. The study was conducted from September, 2019 to June, 2020. The sample of 500 parents (250 mothers & 250 fathers) was selected using purposive sampling. The results of the study revealed that there is a significant positive correlation (r=.83**, p<.01) between social stigma and perceived stress among parents having children with special needs. Findings indicated that mothers experienced higher level of social stigma and perceived stress as compared to fathers. Similarly, parents of children with autismspectrum disorder experienced elevated level of PSS and PS as compared to parents of children with intellectual disabilities and down syndromes. Findings also indicated that Perceived social stigma is a significant predictor of perceived stress [R2 =.691; F (1, 498) = 1115.2, p<.01]. Results concluded that parents need counselling and clinical services to minimize the negative impact of perceived stigma and in order to reduce their stress.